Artificial intelligence is a new revolution in the world of information | الذكاء الاصطناعي ثورة جديدة في عالم المعلومات - Al-Omran | العمران, Hamad bin Ibrahim | حمد بن إبراهيم (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
Artificial intelligence is a field concerned with developing systems and programs capable of carrying out tasks that require human intelligence. Artificial intelligence aims to enhance the analytical, learning and decision-making capabilities of computer systems. Artificial intelligence consists of a group of techniques and tools that aim to learn devices and develop their capabilities in various fields. Among the most important artificial intelligence techniques is machine learning, which allows computer systems to learn from data and analyze it to make smart decisions based on discovered patterns. Machine learning techniques include neural networks. Synthetic, classification, clustering, deep learning, etc. In addition to machine learning, artificial intelligence technologies also include other fields, such as: natural language processing, information retrieval, computer vision, general intelligence, planning, and human-machine interaction. AI applications are used in a variety of fields, including: advanced robotics, medical diagnosis, e-commerce, financial analysis, user recommendations, machine translation, industrial process control, and many others. Artificial intelligence can also play an important role in improving and developing the performance of libraries and information centers. | الذكاء الاصطناعي هو مجال يهتم بتطوير أنظمة وبرامج قادرة على تنفيذ مهام تتطلب ذكاء بشريا، ويهدف الذكاء الًاصطناعي إلى تعزيز القدرات التحليلية وقدرات التعلم واتخاذ القرارات للأنظمة الحاسوبية. يتكون الذكاء الًاصطناعي من مجموعة من التقنيات والأدوات التي تهدف إلى تعلم الأجهزة وتطوير قدراتها في مجالًات متنوعة، ومن أهم تقنيات الذكاء الًاصطناعي: تعلُّم الآلة Machine Learningالتي تسمح للأنظمة الحاسوبية بالتعلم من البيانات وتحليلها لاتخاذ قرارات ذكية بناء على الأنماط المكتشفة، وتتضمن تقنيات تعلم الآلة الشبكات العصبية الًاصطناعية والتصنيف والتجميع والتعلم العميق وغيرها. وبالإضافة إلى تعلم الآلة، تشمل تقنيات الذكاء الاصطناعي أيضا مجالًات أخرى، مثل: معالجة اللغة الطبيعية واسترجاع المعلومات والرؤية الحاسوبية والذكاء العام والتخطيط والتفاعل بين الإنسان والآلة. وتُستخدم تطبيقات الذكاء الًاصطناعي في مجموعة متنوعة من المجالًات، بما في ذلك: الروبوتات المتقدمة، والتشخيص الطبي، والتجارة الإلكترونية، والتحليل المالي، وتوصيات المستخدم، والترجمة الآلية، والتحكم في العمليات الصناعية، والكثير غيرها. ويمكن كذلك أن يكون للذكاء الاصطناعي دور مهم في تحسين وتطوير أداء المكتبات ومراكز المعلومات.